Bivariate Spatial Pattern Based on The Characteristics of Women Smokers in Indonesia - Putri, Diana Rohmandani; Safarudin, Rudi; Khokar, Ammad; Tayab, Konain; Kashif, Muhammad Taaha; Astutik, Erni (citeus, 2023)
The increasing prevalence of smoking among women globally has become a critical public health issue. World Health Organization (WHO) data shows 20 percent of women use tobacco. Women smokers face an increased risk of various diseases. Spatial studies need to be conducted as a basis for planning and providing targeted interventions to reduce the spread of diseases caused by smoking. The study aimed to determine the spatial description of smoking among women in Indonesia. This study analyzed the 2017 IDHS data and used an ecological study design with a descriptive approach and a spatial analysis model. The results are Papua was the province with the highest percentage of women smoking with no education and with the lowest de jure wealth quintile. Provinces using the Internet almost daily were Banten and East Java, and the province with women unemployed in the past 12 months before the survey was North Sulawesi. Based on the results, there are five provinces in Indonesia with a high percentage of smoking among women, assessed by education, internet access, wealth quintile, and non-working women. This study concludes that there is a need to implement smoke-free zones (SFZs), also conduct communication, information, and education (IEC) through mass media.